Discrepancy between mRNA and Protein Expression of Neutrophil Gelatinase-Associated Lipocalin in Bronchial Epithelium Induced by Sulfur Mustard. (20th May 2010) - Ebrahimi, Majid; Roudkenar, Mehryar Habibi; Imani Fooladi, Abbas Ali; Halabian, Raheleh; Ghanei, Mostafa; Kondo, Hisatake; Nourani, Mohammad Reza
Abstract : Sulfur mustard (SM) is a potent vesicant that has been employed as a chemical weapon in various conflicts during the 20th century. More recently, mustard was used in the Iraq conflict against Iranian troops and civilians. At the present time there are more than 40.000 people suffering from pulmonary lesions special bronchiolitis obliterans (BOs) due to mustard gas. SM increases the endogenous production of reactive oxygen species (ROS). Neutrophil Gelatinase-associated Lipocalin 2 (Lcn2, NGAL) is a member of the lipocalin superfamily for which a variety of functions such as cellular protection against oxidative stress have been reported. Ten normal and Twenty SM-induced COPD patient individuals were studied. Assessment of NGAL expressions in healthy and the patients endobrinchial biopsies were performed by semiquantitative RT-PCR, real-time RT-PCR, and Immunohistochemistry analysis. While Normal control samples expressed same level of mRNA NGAL, expression level of mRNA-NGAL was upregulated about 1.4- to 9.8-folds compared to normal samples. No significant immunoreactivity was revealed in both samples. As we are aware this is the first report of induction of NGAL in patients exposed to SM. NGAL may play an important role in cellular protection against oxidative stress toxicity induced by mustard gas in airway wall of patients.